Juvenile delinquent pupils' perceptions on the teaching of Islamic education: a preliminary study - Suhid, Asmawati; Mohd Fakhruddin, Fathiyah; Abdul Mutalib, Lukman; Ahmad, Abdul Muhsin (Human Resource Management Academic Research Society, 2019)
The Islamic Education subject is compulsory for all Muslim pupils in Malaysia. Based on the concept of ‘Education for All’, pupils in the Integrity Schools in Malaysia are also given access to Islamic Education to ensure they are not neglected in the national education development. This is clearly stated in the National Education Philosophy. Therefore, as Malaysian citizens, the delinquent pupils have the right for a comprehensive education. Formal education in Integrity Schools for juvenile delinquents was established in 2008. The pupils are taught Islamic Education, similar to that taught within the national education system. Despite the fact the pupils are regarded as delinquents, they must still be taught and nurtured with Islamic values and morals so they can grow to become responsible individuals in the future. They are the generation that will inherit and shade the colours of the future society. Henceforth, this research seeks to study the perceptions of pupils from the Integrity Schools with regard to Islamic Education, particularly their interests towards it, and the impact it would have on how they practise Islamic values in their lives.